WILLIAM WHEWELL, THE PLURALITY OF WORLDS, AND THE MODERN SOLAR SYSTEM: with Andreas Losch, "Astrotheology: Exoplanets, Christian Concerns, and Human Hopes"; David Wilkinson, "Searching for Another Earth: The Recent History of the Discovery of Exoplanets"; Michael J. Crowe, "William Whewell, the Plurality of Worlds, and the Modern Solar System"; David Dunér, "Swedenborg and the Plurality of Worlds: Astrotheology in the Eighteenth Century"; Ted Peters, "Astrobiology and Astrochristology"; Howard Smith, "Alone in the Universe"; and Lucas John Mix, "Life‐Value Narratives and the Impact of Astrobiology on Christian Ethics.". Issue 2 (June 2016) - Crowe, Michael J.
Abstract: Astronomers of the first half of the nineteenth century viewed our solar system entirely differently from the way twentieth‐century astronomers viewed it. In the earlier period the dominant image was of a set of planets and moons, both of which kinds of bodies were inhabited by intelligent beings comparable to humans. By the early twentieth century, science had driven these beings from every planet in our system except the Earth, leaving our solar system (and perhaps others) as more or less desolate regions for the most part bereft of intelligent life. This essay traces this extinction and its relation to religious thought, noting the role played in it by Sir John Herschel and especially by William Whewell. The inverse square laws for gravitation, heat radiation, and light receive special attention, as does the question of the relevance of the Christian notions of a divine incarnation and redemption.